2011
DOI: 10.12991/201115443
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative alterations during human platelet storage

Abstract: SUMMARY: During storage of platelet obtained by apheresis several changes occur. The aim of this study was to investigate the effect of storage on activation, apoptosis, protein pattern, lipid peroxidation, and the levels of nitric oxide (NO) and glutathione (GSH) of platelets. In this study, platelets obtained from healty donors (n=7) by apheresis were kept in an agitator for nine days at 20-24°C. The samples were taken on the 1st, 3 rd, 5 th and 9 th days and platelets were precipitated. Platelet activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…We also demonstrated significantly lower levels of GSH in gamma‐irradiated PLTs on Days 0, 1, and 3 of storage. Our findings about storage‐dependent decreases in intracellular GSH were in accordance with previous studies 58,62,65 . However, to the best of our knowledge this is the first report that indicated that gamma irradiation decreases intra‐PLT GSH in stored PCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also demonstrated significantly lower levels of GSH in gamma‐irradiated PLTs on Days 0, 1, and 3 of storage. Our findings about storage‐dependent decreases in intracellular GSH were in accordance with previous studies 58,62,65 . However, to the best of our knowledge this is the first report that indicated that gamma irradiation decreases intra‐PLT GSH in stored PCs.…”
Section: Discussionsupporting
confidence: 92%
“…However, they also indicated that, with the significant induction of oxidative state during storage the levels of both GSH and GSSG in 5‐day‐stored PCs reach the comparable amount for both gamma irradiated and untreated controls 29 . Regardless of irradiation effects, several other studies also used GSH levels to monitor PLTs redox state during storage; nonetheless, they evaluated intra‐PLTs GSH rather than the released one, 58,62–65 which may not be an appropriate method to evaluate intracellular redox state. Similar to others here, we examined the intracellular GSH while in both irradiated and nonirradiated PCs gradual decreases of GSH were indicated during storage.…”
Section: Discussionmentioning
confidence: 99%
“…1). This result is consistent with the a study of Goker et al in 2011 where seven platelet concentrates obtained by apheresis showed a significant difference in the concentration of malondialdehyde (MDA) between days 5 and 7 of storage, attributing it mainly to damage caused by ROS to polyunsaturated fatty acids of the membrane [27].…”
Section: Discussionsupporting
confidence: 92%
“…OS leads to decrease in platelet nitric oxide which increases platelet activation and cellular production of reactive oxygen species (ROS) [ 4 ]. But whether resulting oxidative changes trigger activation and apoptosis or activation and apoptosis trigger oxidative changes during storage is still unclear [ 5 ].…”
Section: Introductionmentioning
confidence: 99%